APPLICATION OF RELATED WRITING METHOD WITH ONOMOTOPE TECHNIQUES TO IMPROVE POETRY WRITING ABILITY - Suherman Suherman; Teti Sobari; Rochmat Tri Sudrajat (JLER (Journal of Language Education Research), 2022)
This study aims to determine the effect of the Relay Writing method with the Onomatopoeic technique on writing poetry for class V at Hangan Elementary School. The object of this research is the fifth grade students of SDN Hangan as many as 25 people. This study uses a qualitative descriptive method using triangulation data collection techniques, data analysis is inductive. Based on the results of the initial and final tests, it can be seen that the average score of students on the initial test is 47.6. Meanwhile, the average score of students on the final test, which is 73.2, is in line with the results of the paired sample t-test which obtained a sig(2-tailed) value of 0.00 <0.05 which indicates an effect. So it can be said that there is an increase in the ability of fifth graders at SDN Hangan to write poetry in terms of determining the themes, messages, diction, images and figure of speech contained in poetry, although there are still some students who are not optimal in using pictures and pictures.